1995
DOI: 10.1038/376156a0
|View full text |Cite
|
Sign up to set email alerts
|

Unusual twentieth-century summer warmth in a 1,000-year temperature record from Siberia

Abstract: In the current debate on the magnitude of modern-day climate change, there is a growing appreciation of the importance of long, high-resolution proxies of past climate1-3. Such records provide an indication of natural (pre-anthropogenic) climate variability, either singly at specific geographical locations or in combination on continental and perhaps even hemispheric scales4. There are, however, relatively few records that are well dated, of high resolution and of verifiable fidelity in terms of climate respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
171
4
6

Year Published

1998
1998
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 272 publications
(189 citation statements)
references
References 17 publications
6
171
4
6
Order By: Relevance
“…The tree-ring data in Siberia and Mongolia neighboring the Altay Mountains revealed the similar rise of temperatures form the mid-nineteenth century (Jacoby et al 1996;Briffa et al 2002). The growth of Siberian larch in the Altay Mountains also captures this warming trend (Fig.…”
Section: Tree Growth and Recent Warming Trendsmentioning
confidence: 81%
See 1 more Smart Citation
“…The tree-ring data in Siberia and Mongolia neighboring the Altay Mountains revealed the similar rise of temperatures form the mid-nineteenth century (Jacoby et al 1996;Briffa et al 2002). The growth of Siberian larch in the Altay Mountains also captures this warming trend (Fig.…”
Section: Tree Growth and Recent Warming Trendsmentioning
confidence: 81%
“…In strongly exposed locations, it may be no bigger than a shrub. Several tree-ring chronologies of Siberian larch, as climatic proxy records, have been developed from the Altay Mountains in recent decades (Ovtchinnikov et al 2000;Briffa et al 2002;Frank et al 2007;Myglan et al 2008;Loader et al 2010;Dulamsuren et al 2010;Sidorova et al 2011;Chen et al 2011). In the course of these studies, growth-climate relationships in different regions and across environmental gradients were evaluated (Frank et al 2007;Dulamsuren et al 2010;Chen et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Taken together, the volcanic eruptions may have affected a large area in southwest China. Warming in the 20 th century has been observed in treering reconstructions of temperature from widespread regions of Eurasia (Jacoby et al 1996;Briffa et al 2002;Gou et al 2007;Büntgen et al 2008;Chen et al 2010). Based on instrument data and other proxies, Wang et al (2004) showed that temperature anomalies during the period 1920 -1950 are noticeably positive over China throughout the last century.…”
Section: Discussionmentioning
confidence: 99%
“…Although the available regional temperature records only cover the period from the 1930s to present time, it is likely there was an annual temperature increase at the turn of the 20th century. The circum-Arctic annual air temperature increased between $1900 and 1940s (McBean et al 2004) and the tree-ring measurements from Salekhard (66°50¢ N, 65°15¢ E) in the eastern part of the northern Urals also indicate an increase in summer temperature between 1901(Briffa et al 1995Shiyatov et al 2002). We therefore suggest that the diatom changes observed at the turn of the 20th century were climatically induced.…”
Section: Mitrofanovskoe Lakementioning
confidence: 99%